Effects of pulsed Al injection on InGaN/GaN multi-quantum well structures grown by MOCVD. (23rd July 2021) - Paliwal, Avinash S; Parjapat, Priyavart; Kushwaha, Bhoopendra Kumar; Singh, Kuldip; Mathew, Manish
Abstract: This work presents the effects of tri-methyl-aluminum (TMAl) injection during the metal-organic chemical vapor deposition growth of InGaN multi-quantum wells (MQWs). Three different MQW structures are grown on c -plane sapphire substrate. The grown structures are analyzed using high-resolution x-ray diffractometer, photoluminescence (PL), electroluminescence (EL) and atomic force microscope (AFM) techniques. It is found that MQW structure without TMAl injection is pseudomorphic at room temperature, with peak emission at ∼434 nm and EL at ∼438.8 nm. For TMAl-injected MQWs, partial relaxation is observed in the reciprocal space map. The multi-peak emission wavelengths in PL and EL are observed for TMAl-injected samples. Interestingly, the emission wavelengths are found to be red-shifted. AFM images of the grown MQW structures with Al injection suggest that the grown MQW layers are in 3D form, indicating the formation of nanostructures due to TMAl injection in the MQW layers.